Students' Perceptions in The Implementation of Physical Education Sports and Health at Vocational School Kudus Regency - AMIN, SYAIFUL; Nasuka, Nasuka; Rustiadi, Tri (Journal of Physical Education and Sports, 2021)
The background of this research is the perception of students in physical education learning to be able to express their opinions and ideas as a success in teaching and learning. Research objectives 1) Analyze students' perceptions of the construction of physical education and physical education learning. 2) Analyzing students' perceptions of the implementation of physical education learning at Vocational High School Kudus Regency. The research design in mixed methods research. This research approach is self-inventory. Population was 4 Vocational Schoolin Kudus Regency. Sample was taken by purposive sampling as many as 229 students. The instrument used to collect data is using a questionnaire. The data analysis used is descriptive analysis where if the data has been collected. The results of the study stated that from the results of the category table it can be seen that the roles and perceptions of class X and XI students towards PESH learning are in the very good category with the largest percentage of 88.42%. The roles and perceptions of class X and XI students towards PESH learning are in the very good 25% category, 61% good and the enough category. It can be concluded that the role and position of students towards PESH in 4 SMKs in Kudus Regency shows quite good results in terms of 5 indicators although there are indicators that show good results.